The Impact of LED Colour Rendering on Reaction Time of Human Eyes in Tunnel Interior Zone - Li-Li Dong; Qi Lou; Peng Liu; Wen-Hai Xu (Advances in Civil Engineering)
The long reaction time of human eyes will increase the probability of traffic accidents in tunnels which can be reduced by improving lighting conditions. In recent years, light-emitting diodes (LEDs) have replaced the traditional lighting source in a tunnel. Colour rendering index 2012 (CRI2012, a colour rendering evaluation index) is the most suitable evaluation method for colour rendering of LEDs. In order to study the impact of colour rendering of LEDs on the reaction time of human eyes, a driving simulation environment was designed. First, three CCTs (correlated colour temperatures), four CRI2012s, and eight colours of targets were assessed using mesopic photometry model MES-2. The calculation results indicated that the contrast of targets had a positive correlation with CRI2012 and had a negative correlation with CCT. Then, reaction time experiment was conducted in simulated tunnel environments. There are 30 observers who participated. The results show that the LEDs with higher CRI2012 and lower CCT in tunnel is conducive to reducing the reaction time of human eyes. High CRI2012 enables drivers to accurately and quickly identify colours. This paper provides a reference for the design of light source parameters, roads, walls, and warning signs in the tunnel.